Removal of Azo Dye Carmoisine by Adsorption Process on Diatomite. (9th September 2022) - Labiod, Kotbia; Hazourli, Sabir; Bendaia, Marwa; Tlili, Mohamed; AitBara, Adel; Graine, Radouane; Meradi, Hazem
Abstract : This work aims to evaluate the adsorption capacity of an abundant natural diatomite (ND) to remove the azo dye carmoisine, known as a harmful emerging organic pollutant. Indeed, to the best of our knowledge, no results were reported on this subject. The ND was characterized by FTIR, XRD, and SEM/EDX analyses. The experimental study of adsorption was carried out in batch mode. Results showed that ND adsorbent is mainly composed of silica. A fraction of calcite and ankerite was also identified. It is a porous material with a specific surface of about 41 m 2 .g -1 and with a hydroxyl surface functional group -OH. Adsorption results showed that adsorption process on ND is found to be effective in removing the carmoisine colorant. The adsorption capacity is strongly affected by the adsorbent and adsorbate contents, the solution pH, the work temperature, and the water hardness and mineralization. At room temperature, optimal experimental conditions for the highest adsorption capacity (12 mg.g -1 ) were colorant concentration 50mg.L -1, pH 2, contact time 30min, and ND content 1 g.L -1 . Modeling study has showed that experimental results are well modeled by the Freundlich isotherm in multilayer adsorption. The reaction kinetics are pseudo-second order, and the thermodynamic parameters indicated that the nature of the adsorption process is endothermic and spontaneous.